Valuation methodologies for business startups: a bibliographical study and survey - Batista de Oliveira, Fabrício; Perez Zotes, Luís (Brazilian Journal of Operations & Production Management, 2018)
The aim of this study was to research and analyze the different methodologies used for the valuation process and identify which are the most suitable for startup companies in the Brazilian market. The investigation was carried out by means of bibliographical research articles through the databases Scopus and Web of Science and through interviews with professional experts in valuation of companies. The approach of the subject valuation for business startups, presents plenty of opportunities in the countries of Central and South America by their limited amount of scientific production found in databases of scientific productions. From the market point of view, the article presents important contribution to the promotion and maintenance of startups projects, many of which in the early stage of deployment, since it will serve as a source of consultation for such category of company that needs to identify the better options in the process of valuation for startups and companies as support for the economic and financial viability study of projects in the early stage, supporting the professional segments of Administration, Finance and Engineering Production, not limited only to those. The originality of this research is to make a direct relationship of valuation commonly used with startups definitions proposed by Blank and Dorf (2014) and Ries (2011).